Metabolomic and transcriptomic analyses of drought resistance mechanisms in sorghum varieties - Li Yue; Hui Wang; Qimike Shan; Zaituniguli Kuerban; Hongyan Mao; Ming Yu (PeerJ, 2025)
For a long time, sorghum breeding has focused on improving yield and quality traits, whereas little research has been conducted on drought resistance. To this end, this study evaluated the phenotypes of two sorghum varieties (GL98 and GL220) under drought stress and normal conditions, and sequenced their transcriptomes and metabolomes. After drought stress, the growth rates of the roots and shoots of GL220 exceeded those of GL98 at 72 h. A total of 6,344 differentially expressed genes (DEGs) were identified via RNA-seq differential expression analysis; these genes were significantly annotated in the phenylpropanoid biosynthesis, starch and sucrose metabolism, amino acid metabolism, and flavonoid biosynthesis pathways. The 6,344 DEGs were clustered into four clusters by K-means, and the pathways of each cluster were annotated. A total of 3,913 metabolites were identified by ultrahigh-performance liquid chromatography–MS (UPLC–MS), and a total of 1,942 differentially accumulated metabolites (DAMs), including five common DAMs, were identified. Through combined RNA-seq and metabolomics analyses, we determined that the flavonoid biosynthesis pathway is an important regulatory pathway in the sorghum response to drought stress and that Sobic.007G058600 was significantly correlated with 10 metabolites of the flavonoid pathway. In summary, our results provide a theoretical basis for a deeper understanding of the molecular mechanism of sorghum drought resistance and new genetic resources for subsequent research.